2008
DOI: 10.1016/j.jacc.2007.11.073
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Mobilization by Granulocyte Colony-Stimulating Factor for Myocardial Recovery After Acute Myocardial Infarction

Abstract: Cumulatively, available evidence does not support a beneficial effect of G-CSF in patients with AMI after reperfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
106
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(115 citation statements)
references
References 34 publications
8
106
1
Order By: Relevance
“…The effects of this therapy on LV function and target vessel revascularization are summarized in a recently published metaanalysis by Zohlnhöfer et al They found no effect of an additional G-CSF therapy after myocardial infarction with regard to LV-ejection fraction. Also restenosis or target vessel revascularization was not influenced by this therapy (110).…”
Section: Review Articlementioning
confidence: 79%
“…The effects of this therapy on LV function and target vessel revascularization are summarized in a recently published metaanalysis by Zohlnhöfer et al They found no effect of an additional G-CSF therapy after myocardial infarction with regard to LV-ejection fraction. Also restenosis or target vessel revascularization was not influenced by this therapy (110).…”
Section: Review Articlementioning
confidence: 79%
“…In cellular cardiomyoplasty, according to the cell delivery system, the results are different. Least effective method is mobilization from peripheral blood or bone marrow (170)(171) and most effective method is intracoronary infusion (172)(173). And in case of intravenous infusion, according to the blood flow, all blood in body has to pass the lung and some proportion of infused stem cells are trapped at the lung (174)(175).…”
Section: Discussionmentioning
confidence: 99%
“…However, G-CSF therapy was associated with a lower ejection fraction at 6 cells, G-CSF modulates intracellular signalling cascades within cardiomyocytes and can activate neutrophils, and several trials have been stopped early as a result of excessive in-stent restenosis and acute coronary syndromes in patients with coronary artery disease. [7][8][9][10][11] Animal data have similarly yielded discordant results, depending on the dose and timing of G-CSF.…”
Section: Methodsmentioning
confidence: 99%